Leadership And Creativity Development of the Children’s Forum of Nelayan Seberang Village, Medan Belawan District (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
This service activity aims to realize the 11th SDG regarding sustainable cities and communities through a children's forum. The Children’s Forum of Nelayan Seberang Village, Medan Belawan District, Medan City is an organization acting as a forum for leadership and creativity participation for children in development planning. The forum should implement 2P, namely Pelopor (Pioneer) and Pelapor (Informer). This activity was attended by 12 members of the Children Forum of Nelayan Seberang Village. This service was carried out using the FGD method, training, and mentoring. The FGD results show that the children need to know themselves and increase their confidence to lead and develop themselves. The training results imply that religious and artistic activities are needed to improve the characters and devotions of the members. Leadership development was carried out so they have the awareness to lead themselves, understand the common environmental obstacles, and strive to focus on goals. In addition, creativity development was done to enable them to do new things and motivate themselves to never give up. It is hoped that with the training and mentoring activities, the members of the Children’s Forum of Nelayan Seberang Village can express their aspirations and be involved in making decisions for village development planning.